Crafting and executing strategy : - Thompson, Arthur A. (McGraw-Hill/Irwin, 2007)
The book is particularly suited for courses where the instructor wishes to provide students with a foundation in the core concepts and analytical tools of strategic management and an introduction to the literature of strategic management.